A Legal Analysis of the Supervisory Judge's Authority in Cancelling Asset Auctions in Bankruptcy Processes (Case Study of Supreme Court Decision No. 1863 K/Pdt.Sus-Pailit/2022) - Farahditya, Nabilah Fitroh (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
An inquiry is in progress on the bankruptcy case of PT Rukun Bersama Sentosa and Rangga Prasetya. As both firms are currently undergoing bankruptcy proceedings, a legal investigation into the validity of the asset sale associated with Rangga Prasetya has emerged. The cassation verdict pertains to the Supervisory Judge's competence to annul the auction and enforce the regulations governing auction cancellation in bankruptcy proceedings. This decision was made in accordance with bankruptcy law provisions. The Supreme Court of Indonesia overturned the ruling of the Commercial Court rendered by the Surabaya District Court. The Supreme Court provided direction on the proper implementation of the law in this particular bankruptcy case. The regulations and statutes that define the limits of the Supervisory Judge's jurisdiction and the procedure for the annulment of asset auctions impacting creditors and debtors are referred to as the applicable regulations and laws. This research utilized a methodology known as normative legal analysis, which focuses on positive legal norms, principles, and doctrines. This technique guided the conducted investigation. The methodology was implemented in a case-specific manner. Three main kinds of legal papers can be utilized to access the data sources. These include primary legal resources, secondary legal materials, and tertiary legal materials. This case extends the Supervisory Judge's jurisdiction in bankruptcy proceedings, particularly regarding the annulment of the debtor's assets, so strengthening the legal protections given to debtors filing for bankruptcy.